Ferrites of cobalt and cobalt-zinc for magnetorheological materials: Preparation and properties - Yu.S. Haiduk; E.G. Petrova; J.A. Fedotova; N.M. Lapchuk; A.A. Kharchanka; E.V. Korobko; A.E. Usenka; V.V. Pankov (Next Materials)
Ferrites of cobalt CoFe2O4 and cobalt-zinc Co0.65Zn0.35Fe2O4 were obtained by co-precipitation of aqueous salt solutions followed by thermal and mechanical treatment of precipitates, and studied by X-ray phase analysis, scanning electron microscopy, FTIR spectroscopy and magnetometry. The materials are polydisperse powders with a size of coherent scattering regions of 30–35 nm, and high shear stress in magnetorheological suspensions, which is 4.5 times higher than the corresponding value for nanosized particles. High-temperature annealing leads to a significant increase in the specific magnetization of powders, as well as the shear stress in suspensions prepared on their basis. Doping cobalt ferrite with zinc leads to an increase in the specific magnetization and shear stress of magnetorheological suspensions based on it. The shear stress in suspensions of investigated materials is ∼2.5–4.5 kPa at 625 mT, which allows them to be used as functional fillers for magnetorheological applications.